Observation of Bs 0 mesons and measurement of the Bs 0/B+ yield ratio in PbPb collisions at [Formula presented] TeV - Tumasyan, A. (2022)
The Bs 0 and B+ production yields are measured in PbPb collisions at a center-of-mass energy per nucleon pair of 5.02 TeV. The data sample, collected with the CMS detector at the LHC, corresponds to an integrated luminosity of 1.7 nb−1. The mesons are reconstructed in the exclusive decay channels B→s0J/ψ(μ+μ−)ϕ(K+K−) and B→+J/ψ(μ+μ−)K+, in the transverse momentum range 7–50 GeV/c and absolute rapidity 0–2.4. The Bs 0 meson is observed with a statistical significance in excess of five standard deviations for the first time in nucleus-nucleus collisions. The measurements are performed as functions of the transverse momentum of the B mesons and of the PbPb collision centrality. The ratio of production yields of Bs 0 and B+ is measured and compared to theoretical models that include quark recombination effects.